Analisis Persepsi Masyarakat Terhadap Kinerja Pelayanan Administrasi Pegawai Kantor Desa Kepada Masyarakat (Studi Kasus Di Kantor Desa Sukadana Tengah Kecamatan Sukadana Kabupaten Lampung Timur) - Safrizal, Andi; Lelawati, Nina (Jurnal Manajemen DIVERSIFIKASI, 2022)
Employee performance in providing public services can be seen from several indicators including quality, quantity, timeliness, effectiveness and independence of employees while providing services. The purpose of this study was to analyze the community's perception of the performance of village office employees' administrative services to the community at the Sukadana Tengah Village Office, Sukadana District, East Lampung Regency. The research design is quantitative. The method used is the descriptive analytic method. The object of this research is the quality, quantity, effectiveness, independence and administrative services. This research activity was carried out at the Sukadana Tengah Village Office, Sukadana District, East Lampung Regency. The research population was residents of Central Sukadana Village, Sukadana District, East Lampung Regency with the number of samples taken as many as 96 respondents. Data collection techniques using questionnaires. The analytical tool used is data quality analysis and multiple linear regression analysis with SPSS program. The results showed that the quality, effectiveness, work independence had a positive and significant effect on employee administration services, while the quantity of work had no effect on administrative services. Simultaneously quality, quantity, effectiveness, and work independence simultaneously have a significant influence on administrative services. Keywords:​Quality, Quantity, effectiveness, work independence and Administrative Services